THE CORRELATION AMONG READING STRATEGIES, READING COMPREHENSION ACHIEVEMENT AND GENDER DIFFERENCES OF THE SECOND YEAR STUDENTS OF SMP NEGERI 17 PALEMBANG - Fenny Thresia (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2012)
Abstract: The study was aimed at finding out (1) the reading strategies dominantly used by the second year students (2) whether or not there was significant correlation between students’ reading strategies and reading comprehension achievement (3) whether or not there was any difference between male and female students in terms of reading strategies and reading comprehension achievement, (4) whether or not students’ reading strategies influence reading comprehension achievement. The data were collected using Reading Strategies Questionnaire and a reading test. The findings of the study showed that: first, the students mostly used metacognitive strategies in reading activity. Second, there was a strong and positive correlation between reading comprehension achievement and reading strategies. Third, male and female of students have any significance difference in their reading strategies and their reading comprehension achievement. The last, students’ reading strategies influence their reading comprehension achievement.